The expression 2 divided by 2a can be simplified by dividing the numerator by the denominator. This results in 2 divided by 2a being equivalent to 1/a. This simplification is achieved by dividing the common factor of 2 in the numerator and denominator, leaving 1 in the numerator and a in the denominator.
Oh, dude, so like, when you divide 2 by 2a, you're basically just dividing 2 by 2 times a, right? So, you'd end up with 1/a. It's like dividing a Pizza into 2 slices, but then realizing you have to share those slices with a variable called 'a'. Math, man, it's wild.
2
1
(6ab + 9b)/(2a + 3) = 3b(2a + 3)/(2a + 3) = 3b
2a + 2b = c subtract 2a from both sides 2a - 2a + 2b = c - 2a 2b = c - 2a divide both sides by 2 (2/2)b = (c - 2a)/2 b = (c - 2a)/2 --------------------
2a รทa = 2
2
a/2a^2 You can take "a" out of both of those. It leaves you with 1/2a
1
2
What is 18 divded 5
20 = 1Consider what is the value of 2a ÷ 2a? Any number divided by itself is 1. Thus:2a ÷ 2a = 1The law of indices says that when dividing, they are subtracted, for example:25 ÷ 22 = (2 x 2 x 2 x 2 x 2) ÷ (2 x 2) = 2 x 2 x 2 = 23 = 25-2So 2a ÷ 2a is (also):2a ÷ 2a = 2a-a = 20Since any number subtracted from itself is 0 (= a - a). This must have the same value as before, thus:20 = 1The 2 above can be replaced by any number x which means that any number to the power 0 is 1:x0 = 1
(6ab + 9b)/(2a + 3) = 3b(2a + 3)/(2a + 3) = 3b
2a - 7 = -9 2a - 7 + 7 = -9 + 7 2a = -9 +7 2a = -2 2a/2 = -2/2 a = -2/2 a= -1
2a + 2b = c subtract 2a from both sides 2a - 2a + 2b = c - 2a 2b = c - 2a divide both sides by 2 (2/2)b = (c - 2a)/2 b = (c - 2a)/2 --------------------
3+2*A+B*4/2-4 = 3 + 2A + 2B - 4 = 2A + 2B - 1
2a รทa = 2
(6a3 - 19a2 + 15a)/(2a - 3) = a(6a2 - 19a + 15)/(2a - 3) = a(2a - 3)(3a -5)/(2a -3) = a(3a - 5)